2017
DOI: 10.4067/s0718-95162017005000003
|View full text |Cite
|
Sign up to set email alerts
|

Foliar application of Zinc and Boron improved the productivity and net returns of maize grown under rainfed conditions of Pothwar plateau

Abstract: Under rainfed conditions, farmers rarely use micro-nutrients for crop production, due to which soils become deficient especially in zinc (Zn) and boron (B). Secondly, farmers apply nutrients through soil application but scarcity/less availability of moisture make the nutrients unavailable for crop plants. Under such circumstances, foliar application of Zn and B may play a key role for better crop growth and yield. Therefore this field study was conducted to investigate the role of Zn and B application alone an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
26
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(40 citation statements)
references
References 7 publications
7
26
0
1
Order By: Relevance
“…Plant leaves acted as a source for capturing light and assimilating production. In the current study, plants treated with foliar application of Zn and B mixture produced more LAI with respect to their sole application which might be due to increased indole acetic acid hormone production through micronutrient fertilization as interpreted by Wasaya et al [46].…”
Section: Leaf Area Index (Lai)supporting
confidence: 55%
“…Plant leaves acted as a source for capturing light and assimilating production. In the current study, plants treated with foliar application of Zn and B mixture produced more LAI with respect to their sole application which might be due to increased indole acetic acid hormone production through micronutrient fertilization as interpreted by Wasaya et al [46].…”
Section: Leaf Area Index (Lai)supporting
confidence: 55%
“…Second, the water retention capability of zeolite considerably increases the relative water content of salt-stressed plants by increasing the availability of water and its absorption by roots [62]. On the other hand, our results of growth parameters together with the reports of [63,64] suggest that there is an evident synergistic effect of combining Zn, Si, B, and zeolite nanoparticles leading to improving the vigor of the plants grown under salinity conditions. For example, Panhwar et al [65] reported that combined soil application of Zn and B significantly improved the plant height, root length, chlorophyll concentration, and the dry weight of shoot and root.…”
Section: Of 23mentioning
confidence: 56%
“…2016). According with Wasaya et al (2017), plants with adequate B levels are more tolerant to abiotic stress.…”
mentioning
confidence: 99%